Ecologically valid virtual reality-based technologies for assessment and rehabilitation of acquired brain injury: a systematic review - Faria, Ana Lúcia; Latorre, Jorge; Silva Cameirão, Mónica; Bermúdez i Badia, Sergi; Llorens, Roberto (Frontiers in Psychology, 2023)
Purpose: A systematic review was conducted to examine the state of the literature regarding using ecologically valid virtual environments and related technologies to assess and rehabilitate people with Acquired Brain Injury (ABI). Materials and methods: A literature search was performed following the PRISMA guidelines using PubMed, Web of Science, ACM and IEEE databases. The focus was on assessment and intervention studies using ecologically valid virtual environments (VE). All studies were included if they involved individuals with ABI and simulated environments of the real world or Activities of Daily Living (ADL). Results: 70 out of 363 studies were included in this review and grouped and analysed according to the nature of its simulation, prefacing a total of 12 kitchens, 11 supermarkets, 10 shopping malls, 16 streets, 11 cities, and 10 other everyday life scenarios. These VE were mostly presented on computer screens, HMD’s and laptops and patients interacted with them primarily via mouse, keyboard, and joystick. 25 out of 70 studies had a non-experimental design. Conclusions: Evidence about the clinical impact of ecologically valid VE is still modest, and further research with more extensive samples is needed. It is important to standardize neuropsychological and motor outcome measures to strengthen conclusions between studies.